Sistem Informasi Manajemen Akreditasi Prodi (Simap) Berbasis Web Dengan Instrumen Sembilan Kriteria Pada Universitas Dhyana Pura - I Made Dwi Ardiada; Gerson Feoh; Gabriel Firsta Adnyana; Putu Wida Gunawan; I Nyoman Bernadus; Prastyadi Wibawa Rahayu (Jurnal Tika, 2022)
Dhyana Pura University is a private university under the auspices of the Dhyana Pura Foundation in Badung Regency, Bali. Every study program under the auspices of a university is required to maintain quality assurance through the accreditation process. As for the Study Program accreditation instrument, the data, information and explanation of each requested criteria and parameter are formulated and presented by the study program in an instrument in the form of a guide for filling out study program performance documents (Book IIIA) and a guide for preparing a Self Evaluation Report (LED) or Self Evaluation Report. (SER) (Book IIIB). Each study program at Dhyana Pura University also does not escape efforts to obtain good accreditation status which is carried out in a certain period. The problem that often arises is that data and information related to Study Program Accreditation Instruments are not well organized. If there is no data center (data source) that can be managed periodically, then the recording will occur repeatedly, even though the previous information is very useful in the preparation of the next accreditation form. Therefore, we need an information system that can manage Document Requirements related to Study Program Accreditation. This information system will assist Study Program Management Units and Study Programs in managing study program performance documents and self-evaluation reports according to the Guidelines for Filling Out Performance Documents and Study Program Accreditation Self Evaluation Reports. The information system will speed up the process of accreditation so that the results will be more accurate and save budget, time and costs